2002
DOI: 10.1038/nn993
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of cross-modal binding

Abstract: Little is known about how the brain binds together signals from multiple sensory modalities to produce unified percepts of objects and events in the external world. Using event-related functional magnetic resonance imaging (fMRI) in humans, we measured transient brain responses to auditory/visual binding, as evidenced by a sound-induced change in visual motion perception. Identical auditory and visual stimuli were presented in all trials, but in some trials they were perceived to be bound together and in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
158
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(171 citation statements)
references
References 16 publications
13
158
0
Order By: Relevance
“…2 shows the grand averaged responses obtained for each place-of-articulation condition tested in A, V, and AV conditions in experiment 1. The presence of visual speech (AV condition) significantly reduced the amplitude of the N1 and P2 auditory ERPs compared to auditory-alone conditions (A), in agreement with the deactivation hypothesis (31,32) and contrary to the expectation of supra-additivity.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…2 shows the grand averaged responses obtained for each place-of-articulation condition tested in A, V, and AV conditions in experiment 1. The presence of visual speech (AV condition) significantly reduced the amplitude of the N1 and P2 auditory ERPs compared to auditory-alone conditions (A), in agreement with the deactivation hypothesis (31,32) and contrary to the expectation of supra-additivity.…”
Section: Methodssupporting
confidence: 72%
“…In fact, multisensory integration sites are found throughout the cortex (27), and a fundamental contribution of multisensory neurons may reside in the weighting of one sensory stream against the other, i.e., in reducing stimulus uncertainty (28), rather than in establishing a multisensory perceptual representation. Consistent with this view, complex patterns of activation have been reported that show suppression of sensory-specific cortices (29)(30)(31) in conjunction with enhanced activation of multisensory sites. In congruent AV speech, subadditive interactions in polysensory regions have also been observed (32).…”
Section: Neurophysiological Basis Of Multisensory Integrationmentioning
confidence: 60%
“…Such a result would suggest that distraction is minimized by increasing attention to goal-relevant sensory representations, because orienting attention to a particular stimulus feature increases activity within cortical areas that process that feature (Shulman et al, 1999;Hopfinger et al, 2000;Giesbrecht et al, 2003;Woldorff et al, 2004). Because stimuli presented in different sensory modalities are processed in distinct brain regions (Bushara et al, 2003), the present study provided a particularly clear test of this hypothesis.…”
Section: Introductionmentioning
confidence: 74%
“…3). This system affords the possibility of potential future studies of cross-modal integration both behaviorally and neurophysiologically, topics that have received increased attention of late (5,(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%